2020
DOI: 10.1161/circresaha.120.317362
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Associated Activation of TLR5 Induces Apolipoprotein A1 Production in the Liver

Abstract: Rationale: Dysbiosis of gut microbiota plays an important role in cardiovascular diseases but the molecular mechanisms are complex. An association between gut microbiome and the variance in HDL-cholesterol (HDL-C) level was suggested in a human study. Besides, dietary fat was shown to increase both HDL-C and LDL-C levels. We speculate that certain types of gut bacteria responding to dietary fat may help to regulate HDL-C level and potentially affect atherosclerotic development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Fecal DNA was extracted using the QIAamp DNA Stool Mini Kit (Qiagen, Netherlands), and subjected to whole genome shotgun metagenomic sequencing by Beijing Genomics Institute (Hong Kong, China) as previously described ( Yiu et al, 2020 ). In brief, DNA fragments were sequenced using Illumina HiSeq 4000 (150 bp; paired-end).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fecal DNA was extracted using the QIAamp DNA Stool Mini Kit (Qiagen, Netherlands), and subjected to whole genome shotgun metagenomic sequencing by Beijing Genomics Institute (Hong Kong, China) as previously described ( Yiu et al, 2020 ). In brief, DNA fragments were sequenced using Illumina HiSeq 4000 (150 bp; paired-end).…”
Section: Methodsmentioning
confidence: 99%
“…CCL-98, American Type Culture Collection), were routinely maintained in DMEM/F12K supplemented with 10% FBS. Adenovirus encoding TLR5 (Ad-TLR5) was constructed by Welgen Inc. (MA, United States) as previously described ( Yiu et al, 2020 ). In brief, murine Tlr5 cDNA (GE-Dharmacon, Lafayette, United States) was inserted into pEntCMV-Ef1aGFP vector followed by adenovirus packaging in HEK293 cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary lipid intake, gut microbiota and development of atherosclerosis is linked in mice, which seems to be mediated through the production of inducing metabolites, such as trimethylamine N-oxide (TMAO) (Wang et al 2011 ). TMAO promotes the release of pro-inflammatory cytokines, such as IL-1 β , IL-6 and IL-18 (Seldin et al 2016 ; Yue et al 2017 ), which may be mediated by stimulation of TLR5 by flagellin, which promotes hepatic production of ApoE (Yiu et al 2020 ).…”
Section: Microbiota Impact On Reproducibility Of Various Immunologicamentioning
confidence: 99%
“…Apolipoprotein (Apo), a protein component of plasma lipoprotein, can bind and transport blood lipids to various tissues of the body for metabolism and utilization. It is mainly synthesized in the liver and partly in the small intestine ( Yiu et al, 2020 ). A large number of studies have found that apolipoprotein gene mutation, the formation of different allelic polymorphisms, and further the generation of different phenotypes of apolipoprotein, can affect the metabolism and utilization of blood lipid, thereby triggering the occurrence and development of hyperlipidemia, atherosclerosis, cardiovascular and cerebrovascular diseases ( Richardson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%